If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(4b + 4) + (33b + -9) = 0 Reorder the terms: -8(4 + 4b) + (33b + -9) = 0 (4 * -8 + 4b * -8) + (33b + -9) = 0 (-32 + -32b) + (33b + -9) = 0 Reorder the terms: -32 + -32b + (-9 + 33b) = 0 Remove parenthesis around (-9 + 33b) -32 + -32b + -9 + 33b = 0 Reorder the terms: -32 + -9 + -32b + 33b = 0 Combine like terms: -32 + -9 = -41 -41 + -32b + 33b = 0 Combine like terms: -32b + 33b = 1b -41 + 1b = 0 Solving -41 + 1b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '41' to each side of the equation. -41 + 41 + 1b = 0 + 41 Combine like terms: -41 + 41 = 0 0 + 1b = 0 + 41 1b = 0 + 41 Combine like terms: 0 + 41 = 41 1b = 41 Divide each side by '1'. b = 41 Simplifying b = 41
| 5x+6(x-11)=5(x-12) | | -2=t-3s | | 62+(6x)+(6x+6)=180 | | 16s^2+72s+18=0 | | 12(-82x+26)=84(2x+62) | | 5/3x=56 | | x+5/3=56 | | 4c^2-36c=0 | | 9(3x+6)+(x+2)=11 | | 2n(8n+1)=0 | | 9x+90+y=180 | | x(-5x+2)=24 | | -3u-w=u+7w | | 4x+8+5x-7=180 | | 12+6x=42 | | 6=t+7s | | 6(t-3)+6t=4(3t+5)-12 | | 5x-9x+8=-2+6 | | -2+3x=12 | | -6z-6=-12z+12 | | 9x-6+6x-1+82=180 | | ((-2w^2)/(v^4))^3 | | 5(-2)-2x=20 | | 1/40*n=60 | | 8x^2+21x-28=0 | | 5y+4x=20 | | 1/40*x100=60 | | 2/10x=10 | | x+2=x^2+3x-4 | | x-8.3=-4.5 | | x+2=x^2+2x-4 | | 4x^6-4x^5-8x^4-9x^2+9x+18=0 |